Rivaroxaban in acute venous thromboembolism: UK prescribing experience. Issue 7 (21st October 2021) - Speed, Victoria; Patel, Jignesh P.; Cooper, Derek; Miller, Stephen; Roberts, Lara N.; Patel, Raj K.; Arya, Roopen
Abstract: Background: Rivaroxaban was reported as effective as traditional therapies for the acute treatment of venous thromboembolism (VTE) with fewer major bleeding complications in the seminal Einstein program and is now a recommended option for the treatment of VTE around the world. Objective: To report the safety and efficacy of rivaroxaban in daily care for the management of acute VTE in the United Kingdom. Patients/Method: The FIRST registry is a UK‐only, multicenter, noninterventional, observational VTE study (NCT 02248610). Consecutive patients diagnosed with acute VTE, managed with rivaroxaban, were recruited and followed for up to 5 years. The primary outcomes were treatment‐emergent symptomatic objectively diagnosed recurrent VTE, major and clinically relevant nonmajor bleeding (CRNMB), and all‐cause mortality. Results: A total of 1262 participants were recruited between 2014 and 2018. Participants were heterogeneous, with age range 18 to 95 years, weight 35 to 234 kg, and maximum body mass index 64.4 kg/m 2 . The median duration of treatment exposure was 135 days (interquartile range [IQR], 84‐307) and overall follow‐up 497 days (IQR, 175‐991). There were seven episodes of symptomatic VTE recurrence, 0.6%, (0.74/100 patient‐years; 95% confidence interval [CI], 0.19‐1.28). There were 79 of 1239 (6.4%), 8.66 of 100 patient‐years (95% CI, 6.90‐10.73) first episodes of major or CRNMB, which were most frequently reported by women aged <50 years as abnormal vaginal bleeding. Conclusions: Rivaroxaban is an effective and safe single drug modality for the treatment of VTE in daily practice in the United Kingdom. Data to determine the optimal anticoagulation therapy for women of childbearing age are needed.